MANAGEMENT OF BACTERIAL PLAQUE-INDUCED GINGIVAL ENLARGEMENT: CASE REPORT - Amalia, Martina; Ningsih, Cut Ati; Meydhiono, Widianto (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Gingival enlargement is a condition that we often encounter in the oral cavity. This condition can be caused by plaque accumulation, systemic disorders, and side effects of some drugs as well as genetic factors. Gingival enlargement due to the accumulation of bacterial plaque generally shows signs and symptoms of inflammation which can be a major risk factor for periodontitis. This case report aims to describe two cases of plaque-induced gingival enlargement, one of which was accompanied by the presence of granulomatous epulis. Case: The first case was a 23-year-old woman complaining that her gums often bleed when brushing her teeth since 1 year ago. Intra oral examination can see swelling of the gingiva in the anterior area of RA and RB. The second case is a 40-year-old woman with complaints of swelling of the lower right back gum since 2 years ago. An enlargement of the gingiva in the anterior area is seen accompanied by granulomatous epulis with fibrous consistency in the posterior area of RB. Treatment: In the first case, non-surgical treatment was carried out and continued with regular visits every 3 months. In the second case, non-surgical and surgical procedures were performed. Treatment begins with tooth root extraction and scaling and root planning. Furthermore, gingivectomy surgery was performed to excise the enlarged gingiva. Discussions: The treatment results look good, where it can be seen that the etiological factor can be ruled out. After the surgical treatment, the healing went well, marked by no inflammation around it. Conclusion: Gingival enlargement can affect aesthetics and interfere with the patient's masticatory function. Identification of the etiological factors is necessary for an appropriate treatment plan.